ISO 45001 Implementation How to Become an Occupational Health and Safety Champion. - Soltanifar, Mehrdad (Milton : Productivity Press, 2022)
Over two million people worldwide die every year due to work-related accidents and illness, which corresponds to over 6000 deaths every day (International Labour Organisation, 2020). Globally, there are about 340 million occupational accidents and 160 million victims of work-related injuries and illness each year (International Labour Organisation, 2020). Occupational health and safety is a major challenge for many organizations. Regardless of the size and nature of their business, organizations should protect their people and provide a safe and healthy working environment. They should identify the potential health and safety risks present in their workplace and take appropriate action to keep their workers free from harm. Occupational safety focuses on potential safety hazards that can cause injury. Occupational health, on the other hand, looks at potential health issues such as occupational medicine, occupational hygiene, and primary health care, including the wellbeing of workers. For organizations that want to implement an occupational health and safety management system based on the ISO 45001:2018 standard but are not familiar with its structure and definitions, it often takes a significant amount of resources to understand the requirements of the standard and plan their implementation. This book provides guidance in establishing an occupational health and safety management system linked to the requirements of ISO 45001:2018. It aims to explain all the requirements of ISO 45001:2018 clause by clause to provide guidance to: Organizations preparing for ISO 45001:2018 implementation Individuals who want to build a career in occupational health and safety Health and safety practitioners and managers who want to improve their occupational health and safety performance Occupational health and safety consultants who prepare their clients for ISO 45001:2018 certification audits Internal and external auditors who audit occupational health and safety management systems. In addition to the requirements of the standard, this book includes industry best practices, methods, and techniques to address these requirements. While clarifying each requirement of the standard, it also discusses the steps needed to achieve the requirement, areas that auditors may check, and mandatory or voluntary documents that may be maintained or retained to demonstrate conformity with the requirement.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Industrial hygiene -- Management -- Standards; Industrial safety -- Management -- Standards; BUSINESS & ECONOMICS / Production & Operations Management; TECHNOLOGY / Industrial Health & Safety; BUSINESS & ECONOMICS / Training